Self‐Healable, Malleable, Ecofriendly Recyclable and Robust Polyimine Thermosets Derived from Trifluoromethyl Diphenoxybenzene Backbones. Issue 18 (22nd February 2023) - Yu, Ping; Wang, Haiyue; Wang, Yi; Liu, Dapeng; Xin, Yumeng; Li, Ruiguang; Jia, Xuemeng; Liu, Lin; Zhang, Dongen; Wang, Chunyu; Zhao, Jun; Zhang, Zhaoming; et al.
Abstract: Dynamic covalent chemistry opens up great opportunities for a sustainable society by producing reprocessable networks of polymers and even thermosets. However, achieving the closed‐loop recycling of polymers with high performance remains a grand challenge. The introduction of aromatic monomers and fluorine into covalent adaptable networks is an attractive method to tackle this challenge. Therefore, we present a facile and universal strategy to focus on the design and applications of polyimine vitrimers containing trifluoromethyl diphenoxybenzene backbones in applications of dynamic covalent polymers. In this study, fluorine‐containing polyimine vitrimer networks (FPIVs) were fabricated, and the results revealed that the FPIVs not only exhibited good self‐healability, malleability and processability without the aid of any catalyst, but also possessed decent mechanical strength, superior toughness and thermal stability. We hope that this work could provide a novel pathway for the design of high‐performance polyimine vitrimers by recycling of plastic wastes. Abstract : FPIVs films were successfully fabricated and evaluated. Owing to the presence of aromatic monomers and fluorine effect as well as the high cross‐linking density of dynamic imine bonds, FPIVs films not only exhibited superior mechanical properties and self‐healable behavior but also realized closed‐loop recycling.